Application of 3D documents in the land cadastre: problems of legal regulation - Maria Zakharova (Геоконтекст, 2021)
The article considers the use of 3D documents in electronic document management and land cadastre. Earth audit (cadastre) within the "Digital Earth" is carried out through 3D documents. The technical nature of 3D documents is clear, but the legal regime is quite complex and poorly understood. In this situation, it is impossible to conduct an audit of the Earth through a 3D document without establishing its legal regime. This article identifies possible ways to develop domestic legislation in the field of digitalization on the example of a 3D document and makes suggestions for improving the current legislation and defining the legal regime of a 3D document, including in relation to the land cadastre.